UNDERSTANDING THE PSYCHOLOGICAL AND SOCIAL DYNAMICS OF CONSUMER APPEARANCE DECISION: FOUNDATIONS FOR A BRANDING FRAMEWORK FOR REKAH - Tania Azahra; Ilma Aulia Zaim (RADJA PUBLIKA, 2026)
The research is guided by three questions: how consumers describe the psychological and social pressures they experience when making appearance decisions in visible settings; how these pressures shape the emotions and self-presentation concerns associated with the possibility of repeating outfits; and how consumers interpret the potential role of a sustainable-fashion brand in supporting these decisions. The underlying assumption is that appearance behaviour must be understood through lived experience rather than through attitudes alone. A qualitative and exploratory methodology was used. Fifteen in-depth interviews, one focus-group discussion, and field-note observations were conducted with young women in urban Jakarta who regularly navigate visible social environments. Using open and axial coding, themes were identified and triangulated across data sources. Five theoretical lenses guided interpretation: Impression Management Theory, Subjective Norms and Perceived Behavioural Control within the Theory of Planned Behavior, Self-Efficacy Theory, Appearance-Related Anxiety, and Brand Trust Theory. Findings reveal five recurring patterns. First, participants feel observed and implicitly evaluated when repeating outfits, reflecting strong subjective norms. Second, emotional discomfort such as embarrassment or nervousness often accompanies decisions to rewear clothing in visible contexts. Third, many participants report low styling confidence, making it difficult to create varied looks from existing wardrobes. Fourth, social-media environments amplify comparison pressures and increase sensitivity to being seen in familiar outfits. Fifth, participants perceive limited brand reassurance or styling guidance, noting that most fashion brands emphasise novelty rather than garment longevity. These patterns highlight that sustainable wardrobe behaviour is shaped not only by environmental attitudes but also by social interpretation, emotional vulnerability, styling uncertainty, and weak brand cues. To address this, the study develops a conceptual branding prototype for REKAH titled “Confident Repetition,” which consists of three strategic pillars: social reassurance and cultural reframing, simple and supportive styling guidance, and transparent sustainability values and trust signals. This prototype offers an initial direction for REKAH to support users in feeling more comfortable, confident, and intentional in their appearance decisions.